2007
DOI: 10.1017/s0950268807008941
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimation of hepatitis E virus seroprevalence for populations with different exposure levels to swine in The Netherlands

Abstract: SUMMARYHepatitis E virus (HEV) is ubiquitous in pigs worldwide and may be zoonotic. Previous HEV seroprevalence estimates for groups of people working with swine were higher than for control groups. However, discordance among results of anti-HEV assays means that true seroprevalence estimates, i.e. seroprevalence due to previous exposure to HEV, depends on choice of seroassay. We tested blood samples from three subpopulations (49 swine veterinarians, 153 non-swine veterinarians and 644 randomly selected indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 31 publications
(44 reference statements)
6
85
0
1
Order By: Relevance
“…Pigs can be infected through direct contact with infected animals, or via feed and water contaminated with faeces. The basic reproduction ratio (R0) is 8.8, which means that one infected animal can be the source of infection for eight other animals (2). HEV infection in swine is subclinical and is observed for approximately 10 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Pigs can be infected through direct contact with infected animals, or via feed and water contaminated with faeces. The basic reproduction ratio (R0) is 8.8, which means that one infected animal can be the source of infection for eight other animals (2). HEV infection in swine is subclinical and is observed for approximately 10 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a comparison of five serological tests showed that the agreement between the tests was moderate at best (kappa y0 . 5) [22]. A couple of IgG enzyme-linked immunosorbent assay (ELISA) commercial kits were withdrawn from the market or replaced by new tests by the manufacturer due to recognition of a high proportions of false-negative results [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…A positive RT-PCR after a minimum of 3-6 mo from the time of diagnosis of HEV, establishes the presence of chronic HEV [24][25][26] . This is because spontaneous clearance may occur within the first 6 mo as noted in initial followup studies in immunosuppressed patients with positive HEV RNA [22,23] . However, recently [24] , Kamar et al [24] reported that in transplant recipients who acquired HEV infection, none of the patients cleared the virus between 3 and 6 mo.…”
Section: Presentation Of Chronic Hepatitis Ementioning
confidence: 95%
“…The reasons for this high seroprevalence could be due to subclinical infection, exposure to animals, serological cross reactivity with other agents or false positive results. In particular, individuals coming in contact with swine, like veterinarians, pig breeders and slaughter house personnel have been found to have statistically significant higher rates of hepatitis E seropositivity in developed countries [18][19][20][21][22] .…”
Section: Virology Epidemiology and Transmissionmentioning
confidence: 99%